Correlation between Doctor-Patient Communication with Patient Satisfaction and Loyalty - Nancy S. Lampus; Dewi S. S. Wuisan (Medical Scope Journal, 2024)
Abstract: Effective communication between doctors and patients has been recognized as a key factor in influencing the patient’s experience during treatment and will affect patient loyalty. This study aimed to investigate and analyze the correlation between doctor and patient communication with patient satisfaction and loyalty, in the context of health services. This was a cross-sectional study using a questionnaire as an instrument to collect data from several patients receiving outpatient treatment at the cardiovascular unit at XYZ Hospital. Data were analyzed multivariate using the PLS-SEM statistical method with SmartPLS®4 software. The results were obtained from 182 respondents who met the inclusion criteria taken in 2023 by purposive sampling with a questionnaire from individuals who had received cardiovascular outpatient services at XYZ Hospital. The five aspects of doctor communication skills were proven to have significant and positive effects. The strongest influence was shown in the empathy factor of communication by a doctor (R2 = 0.274; p-value 0.011; CI 0.086 – 0.479). This study proved the positive impact of patient satisfaction on patient loyalty at XYZ Hospital. From the findings of this study, managerial implications could be drawn for the development of doctors’ communication skills with patients, maintaining doctor quality, and strengthening the hospital image by providing the best services for patients. In conclusion, effective communication plays an important role in increasing patient satisfaction and loyalty toward health services in hospitals. It is necessary to maintain and improve skills in doctor-patient communication. Keywords: effective communication; patient satisfaction; patient loyalty